2023
DOI: 10.1001/jamanetworkopen.2023.13006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Secondhand Smoke Exposure and Myopia Among Children Aged 6 to 8 Years in Hong Kong

Abstract: ImportanceSecondhand smoke (SHS) exposure potentially threatens ocular health; however, its association with myopia is unknown.ObjectiveTo examine the association between SHS exposure and childhood myopia.Design, Setting, and ParticipantsCross-sectional data from the population-based Hong Kong Children Eye Study were used. Data were collected from March 5, 2015, to September 12, 2021, at The Chinese University of Hong Kong Eye Center. Participants included children aged 6 to 8 years. Secondhand smoke exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The possible pharmacological causal pathway mediated via both nicotinic agonist and antagonist was also ill-defined [ 229 , 230 ]. Recently, a large cross-sectional study on 6–8-year-old Hong Kong children has shown an association of second-hand smoking exposure with both the onset and progression of myopia [ 231 ]. A small but dose-response effect of smoking was observed with an increase in 0.07 D myopia or 0.04 mm AL elongation with 10 cigarettes/day [ 231 ].…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
See 1 more Smart Citation
“…The possible pharmacological causal pathway mediated via both nicotinic agonist and antagonist was also ill-defined [ 229 , 230 ]. Recently, a large cross-sectional study on 6–8-year-old Hong Kong children has shown an association of second-hand smoking exposure with both the onset and progression of myopia [ 231 ]. A small but dose-response effect of smoking was observed with an increase in 0.07 D myopia or 0.04 mm AL elongation with 10 cigarettes/day [ 231 ].…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…Recently, a large cross-sectional study on 6–8-year-old Hong Kong children has shown an association of second-hand smoking exposure with both the onset and progression of myopia [ 231 ]. A small but dose-response effect of smoking was observed with an increase in 0.07 D myopia or 0.04 mm AL elongation with 10 cigarettes/day [ 231 ]. The study was cross-sectional in design and could not prove a causal relationship.…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…Chua SY et al found that exposure to passive smoking in Asian children from birth to 6 months of age slightly increases the risk of earlyonset myopia 31 . Another study in Hong Kong indicated that exposure to secondhand smoke was associated with higher myopic refraction, longer axial length, a greater probability of developing moderate and high myopia, and earlier onset of myopia 32 .However, S-M Saw's study did not nd a relationship between parental smoking and childhood refractive errors 33 .This MR study supports for the rst time a causal association between smoking initiation and myopia after adjusting for type 2 diabetes and BMI. This nding suggests that in addition to focusing on children's passive smoking, the initiation of children's smoking also deserves our attention in the eld of myopia development.It is worth noting that considering smoking's potential detrimental effects on the physical development of adolescents, we do not advocate smoking as a means of managing myopia.…”
Section: Discussionmentioning
confidence: 71%
“…The main ways in which environmental pollutants enter the human body are through inhalation, ingestion and skin contact [3] . Some pollutants can also enter the human body through the mucous membranes of the eyes [4] , sweat glands and damaged wounds [5] . They can cause damage to multiple body systems and threaten human health (Fig.…”
Section: Introductionmentioning
confidence: 99%